Analysis of Mobile Ad Hoc Network Resistance to Nodes Defects - Piotr BEDNAREK; Jerzy LOPATKA (Communications of International Proceedings, 2021)
The aim of this study is to determine the resistance of the MANET (Mobile Ad ’hoc Network), to structural defects caused by network nodes failures that reduce the performance of the network. The metrics used in networks monitoring are proposed and implemented in the MANET network simulator. Next an analysis of the results for 2 the test scenarios are presented.
Keywords: MANET; Resistance to Defects; Clusters; Metrics.